Analisis Kinerja Bank Digital yang Terdaftar di BEI Menggunakan Metode EVA, MVA, SVA: Studi Kasus pada Bank Digital Periode 2021-2024 - Arinda Nanda Aprilia; Taufik Akbar; Zulfia Rahmawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze the performance of digital banks listed on the Indonesia Stock Exchange (IDX) using the Economic Value Added (EVA), Market Value Added (MVA), and Shareholder Value Added (SVA) methods during the period 2021 to 2024. The data analyzed includes the financial performance of five digital banks, namely PT. Bank Jago Tbk (ARTO), PT. Allo Bank Indonesia Tbk (BBHI), PT. Bank Aladin Syariah (BANK), PT. Bank Neo Commerce (BBYB), and PT. Bank Amar Indonesia Tbk (AMAR). This study uses quantitative methods to measure bank performance based on three different value-added indicators. The research sample was taken from the annual financial reports of these digital banks. Based on research results for the 2021-2024 period, PT. Bank Jago Tbk shows a stable and positive performance, consistently creating economic value added (EVA) and maintaining solid market value (MVA). However, behind this stability lies a worrying trend, with shareholder value (SVA) turning negative since 2022. On the other hand, PT. Allo Bank Indonesia Tbk shows a picture of extreme volatility after experiencing massive losses in 2022. The bank was able to bounce back and record a strong EVA recovery, even though its market value (MVA) consistently remained in negative territory and continued to decline. Based on these findings, it is concluded that the survival of digital banks is highly dependent on their ability to innovate and maintain operational efficiency, which needs to be supported by a clear regulatory framework. It is also recommended that future research explore the dynamics of this industry in greater depth through broader qualitative variables and approaches.